Creation of a collection of blood samples of patients with multiple myeloma - N. V. Gnennaya; S. V. Timofeeva; A. O. Sitkovskaya; I. A. Novikova; I. B. Lysenko; I. A. Kamaeva; O. I. Kit (Кардиоваскулярная терапия и профилактика, 2022)
Aim. To create a collection of samples of blood components of patients with multiple myeloma for potential fundamental and applied biomedical research.Material and methods. The material was collected according to the developed algorithm, including the collection of clinical information, biological material, sample preparation, quality control and storage in the biobank of the National Medical Research Center of Oncology.Results. As of August 2021, the cryostorage of the National Medical Research Center of Oncology biobank contains a collection of 175 samples of blood serum, plasma and mononuclear cell fraction of patients with multiple myeloma. Samples were obtained from 32 patients of both sexes, the mean age of which was 59,5±1,65 years. To create an electronic catalog, personal, clinical and laboratory data about patients were collected, after which each sample was assigned its own unique identification number. Written informed consent was obtained from all patients for the storage of their biomaterial in a biobank with possible subsequent use for scientific purposes. Freezing of the obtained samples was carried out in accordance with low-temperature storage protocol. The electronic catalog contains a wide range of systematized clinical and laboratory information on samples.Conclusion. The collection of multiple myeloma samples is a unique resource for potential research on its pathophysiology, the development of diagnostic biomarkers, and the search for targeted agents.